Cyclodextrins Exert a Ligand-like Current Inhibitory Effect on the KV1.3 Ion Channel Independent of Membrane Cholesterol Extraction - Kovacs, Tamas; Sohajda, Tamas; Szente, Lajos; Nagy, Peter; Panyi, Gyorgy; Varga, Zoltan; Zakany, Florina (Frontiers in Molecular Biosciences, 2021)
Cyclodextrins (CDs) are cyclic oligosaccharides capable of forming water-soluble complexes with a variety of otherwise poorly soluble molecules including cholesterol and different drugs. Consistently, CDs are widely used in research and clinical practice to deplete cholesterol from cellular membranes or to increase solubility and bioavailability of different pharmaceuticals at local concentrations in the millimolar range. Effects of CDs exerted on cellular functions are generally thought to originate from reductions in cholesterol levels. Potential direct, ligand-like CD effects are largely neglected in spite of several recent studies reporting direct interaction between CDs and proteins including AMP-activated protein kinase, β-amyloid peptides, and α-synuclein. In this study, by using patch-clamp technique, time-resolved quantitation of cholesterol levels and biophysical parameters and applying cholesterol-extracting and non-cholesterol-extracting CDs at 1 and 5 mM concentrations, we provide evidence for a previously unexplored ligand-like, cholesterol-independent current inhibitory effect of CDs on KV1.3, a prototypical voltage-gated potassium channel with pathophysiological relevance in various autoimmune and neurodegenerative disorders. Our findings propose that potential direct CD effects on KV channels should be taken into consideration when interpreting functional consequences of CD treatments in both research and clinical practice. Furthermore, current-blocking effects of CDs on KV channels at therapeutically relevant concentrations might contribute to additional beneficial or adverse effects during their therapeutic applications.